Analisis Sifat Fisik Dan Kimia Buah Salak Pangu (Salacca zalacca) Dengan Pelilinan Selama Penyimpanan - Vina H. Manurung; Gregoria S.S. Djarkasi; Tineke M. Langi; Lana E. Lalujan (Universitas Sam Ratulangi, 2013)
ABSTRACT The purpose of this research was to analyze the physic’s changing and chemistry’s changing of snake fruit that saved in normal temperature and covered by wax. This research was done in laboratory in agriculture technology ± 4 months. This research was using random design complete factorial by mixing wax emulsion and storage time. A treatment ( mixing ratio ) A1 : 1 (wax) : 2 (air), A2 : 1 (wax) : 4 (water), A3 : 1 (wax) : 6 (water) and B treatment (storage time), B1 : 0 day, B2 : 3days, B3 : 6 days, B4 : 9 days, that saved in normal temperature. Then, doing physic analyze such as texture, weight, brightness. And chemical analyze such as sucrose, acidity, water content. The result of this research was shown the worst texture of snake fruit which saved in normal temperature until the nine days was in ratio 1 : 4 ( 5,21 kg) and the highest in ratio 1 : 2 (6,34 kg). the highest weight was in ratio 1 : 4 (67,67%) and the lowest weight was in ratio 1 : 6 (51%). The highest brightness was in ratio 1:6 (29,88%) and he lowest brightness was in ratio 1 : 4 ( 29,35%). The highest of sucrose was in ratio 1:2 (14,16%) and the lowest of sucrose was in ratio 1 : 4 (13,33%). The highest acidity was in ratio 1 : 4 (12,33%), and the lowest acidity was in ratio 1 : 2 (11,8%). The highest water content was in ratio 1 : 4 (43,33%) and the lowest water content was in ratio 1 : 6 (43,01%). Thus, the snake fruit which waxed with ratio 1:4 in 9 days storage showed the best quality. Key Word : snake fruit, storage, waxing